Economics of Onion Production in Region of (Al Salamia) (Journal of Hama University, 2021)
The Onion crop is one of the important vegetable crops in Syria, as it contributes to securing good incomes for farmers, providing job opportunities for the rural population, and improving the economic returns for the producers. In general, the study aimed to study the current productive reality of Onions in Hama Governorate, (189) forms were collected from (Al-Salamiyah) and its villages for the agricultural season (2017-2018). The results of the study showed that (41.3)% of respondents are aged Between (54 - 69) years, the more the age of the farmer increased by one year, the higher the productivity by (3.5) kg / d, and that was significantly at the level of %5. Kg / d compared to traditional irrigation methods, and adding one kg of fertilizer increases productivity by (10.3) kg / d. The average total costs of onion production reached (228514) SP / d and the average profit achieved is (131486) SP / d, while the cost of 1 kg on average was (126.95) SP, total economic efficiency (1.57) and the overall average profitability on average %(57.5), And accordingly, the economic evaluation of Onion production in the study area indicates that he has won during the period studied. The study also showed that the cost of transportation significantly affected costs, at a significant level at the level of significance of %1, and the cost of fertilizers was of great importance in increasing costs, as well as the cost of irrigation water, while excluding the cost of control materials and the cost of harvest and the cost of packages because there was no significant effect on Costs. It was also noticed that the agricultural production costs required to carry out all the service operations needed by the crop were observed, which constitutes an obstacle for farmers to produce the crop with the required quality, and by using the economic standard models for the cost functions according to the determined size of the economic efficiency, which reached (5870) kg, while the most profitable production has reached (6041) kg, while the actual production reached (5580) kg, and by comparing these sizes with the average actual production of the studied area, it was found that it is much less than the most profitable size and relatively less than the optimal size.